(3GdJeKjd hGdeMGVQI HGdCHjGJ GdeaQOI GdfGOQIs - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s ((3eMehO YHO GdQGRb GdfGHdSi s)
(3ChdgG (B:s
(3CeG HYO (B: (3agPG YbO cdg OQQ ajg ef GdeYGfi GdLjGO cd eYfi eHJcQ LeYJ ajg ef GdCHjGJ GdeaQOI eG jJeKd Hg hSejJg s
(3BNQgG (B:s
(3jhGJjc GdUHGM HfG JQLi hjCJjc GdeSGA HeG JTGA s
(3Cdag hCgOGg Edi SdWGf GdeZQH GdCbUi GdZGdH HCeQ Gddg GdTQja YHO Gddgs
(3GdeDda gh eVi GdMQejfs
(3GdfSNI HgG MhGT s
(3HgG JYdjbGJ cKjQI HfaS Gdbde GdJi cJHJ Hg s
(3hHChdgG Jedc hhba s
(3QJHg GdeDda Ydi MQha GdeYLe eYJHQkG ChGFd GdCHjGJ s
Keywords: (3GdCOHs